Plantas de cobertura no desenvolvimento e produtividade da cultura da soja e milho na região do cerrado - Anselmo, Jefferson Luis [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The application of conservation practices aims not only the maintenance and / or improvement of soil quality, as well as the organization and the occupation of the productive areas of the landscape in order to ensure the establishment of the main ecological and hydrological processes and minimize significant impacts caused to the environment . The objective of this study was to evaluate the effect of cover crops grown in the off season and in the development of cultivated maize grain yield in the first crop and soybean tillage system in the Cerrado region. The experiment was carried out in 2010/11 and 2011/12 crop years the Foundation of the experimental area for the Support of Agricultural Research of Plain, located in the municipality of South Chapadão, State of Mato Grosso do Sul, with an altitude of 810 m. The experimental design was a randomized block design with four replications and seven treatments constituted as follows: 1- Zea mays; 2- Zea mays + Urochloa ruziziensis; 3 - Sorghum bicolor; 4 - Crotalaria spectabilis; 5 - U. bryzantha; 6 - Raphanus sativus L., 7 - Pennisetum americanum and 8 - fallow. Corn in single or in consortium with Urochloa ruziziensis cultivation becomes spoiled by cover crops for Direct Planting System, due to its good maintenance of straw on the soil surface; cultural remains of forage turnip and Urochloa bryzantha provided productivity increase in the cultivated maize in the first season in the Cerrado region; the Corn debris, Crotalaria spectabilis and sorghum provided productivity increase in soybean of summer

A aplicação de práticas conservacionistas visa não só a manutenção e/ou melhoria da qualidade do solo, mas também minimizar significativos impactos ocasionados ao ambiente. O objetivo deste trabalho foi verificar a influência da decomposição de plantas de cobertura no desenvolvimento e produtividade da cultura da soja e milho em sucessão, na região do Cerrado. O experimento foi conduzido nos anos agrícolas de 2010/11 e 2011/12, nas áreas de pesquisa da Fundação Chapadão em Chapadão do Sul -MS, 18° 41' S e 52° 40' W, sendo implantadas com um delineamento em blocos ao acaso, com oito tratamentos e quatro repetições. Os tratamentos foram assim constituídos: 1- milho (Zea mays); 2- milho (Zea mays) + Urochloa ruziziensis; 3 - sorgo (Sorghum bicolor); 4 - Crotalaria spectabilis; 5 - Urochloa bryzantha; 6 - nabo forrageiro (Raphanus sativus) L.; 7 - milheto (Pennisetum americanum) e 8 - pousio. O milho em cultivo solteiro ou em consórcio com U. ruziziensis propiciam satisfatória cobertura, pela manutenção de palhada sobre a superfície do solo; os restos culturais de Raphanus sativus e U. bryzantha proporcionaram maior incremento de produtividade na cultura do milho cultivado na primeira safra na região do Cerrado; os restos culturais de milho, C. spectabilis e Sorghum bicolor proporcionaram maior incremento de produtividade na cultura da soja de verão
Keywords: Milho - Nutrição; Soja - Nutrição; Plantio direto; Cultivos de cobertura; Cover crops